Predicting the locations of possible long-lived low-mass first stars: importance of satellite dwarf galaxies - Magg, Mattis; Hartwig, Tilman; Agarwal, Bhaskar; Frebel, Anna; Glover, Simon; Griffen, Brendan F.; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The search for metal-free stars has so far been unsuccessful, proving that if there are surviving stars from the first generation, they are rare, the